2011
DOI: 10.1007/s00467-011-1924-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary ß2-microglobulin in very preterm neonates with chorioamnionitis

Abstract: It is important to identify premature infants with prenatal inflammation as it contributes to short- and long-term complications. Our object was to study how prenatal inflammation affects the urinary β(2)-microglobulin (β(2)-MG) level. Preterm neonates were divided based on the presence of chorioamnionitis (CAM) into the CAM (n = 100) and non-CAM groups (n = 117). These were further subdivided into five groups each: 30 preterm neonates of 23-26; 42 neonates of 27-28; 54 neonates of 29-30; 51 neonates of 31-32;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…When the ability of the proximal tubules to reabsorb albumin from the ultrafiltrate is exceeded, there is increased excretion of albumin in the urine. Nishimaki et al (16) found that, in preterm infants, the urinary beta-2 microglobulin level at 48 h after birth was significantly higher in those with chorioamnionitis than in those without chorioamnionitis. Also, hypoalbuminemia has been shown to be associated with increased risk of necrotizing enterocolitis (17).…”
Section: Discussionmentioning
confidence: 99%
“…When the ability of the proximal tubules to reabsorb albumin from the ultrafiltrate is exceeded, there is increased excretion of albumin in the urine. Nishimaki et al (16) found that, in preterm infants, the urinary beta-2 microglobulin level at 48 h after birth was significantly higher in those with chorioamnionitis than in those without chorioamnionitis. Also, hypoalbuminemia has been shown to be associated with increased risk of necrotizing enterocolitis (17).…”
Section: Discussionmentioning
confidence: 99%